AGE–RAGE Stress, Stressors, and Antistressors in Health and Disease - Prasad, Kailash; Mishra, Manish (International Journal of Angiology, 2018)
Adverse effects of advanced glycation end-products (AGEs) on the tissues are through nonreceptor- and receptor-mediated mechanisms. In the receptor-mediated mechanism, interaction of AGEs with its cell-bound receptor of AGE (RAGE) increases generation of oxygen radicals, activates nuclear factor-kappa B, and increases expression and release of pro-inflammatory cytokines resulting in the cellular damage. The deleterious effects of AGE and AGE–RAGE interaction are coined as “AGE-RAGE stress.” The body is equipped with defense mechanisms to counteract the adverse effects of AGE and RAGE through endogenous enzymatic (glyoxalase 1, glyoxalase 2) and AGE receptor-mediated (AGER1, AGER2) degradation of AGE, and through elevation of soluble receptor of AGE (sRAGE). Exogenous defense mechanisms include reduction in consumption of AGE, prevention of AGE formation, and downregulation of RAGE expression. We have coined AGE and RAGE as “stressors” and the defense mechanisms as “anti-stressors.” AGE–RAGE stress is defined as a shift in the balance between stressors and antistressors in the favor of stressors. Measurements of stressors or antistressors alone would not assess AGE–RAGE stress. For true assessment of AGE–RAGE stress, the equation should include all the stressors and antistressors. The equation for AGE–RAGE stress, therefore, would be the ratio of AGE + RAGE/sRAGE + glyoxalase1 + glyoxalase 2 + AGER1 +AGER2. This is, however, not practical in patients. AGE–RAGE stress may be assessed simply by the ratio of AGE/sRAGE. A high ratio of AGE/sRAGE indicates a relative shift in stressors from antistressors, suggesting the presence of AGE–RAGE stress, resulting in tissue damage, initiation, and progression of the diseases and their complications.
Keywords: advanced glycation end-products (AGE); receptor for AGE (RAGE); soluble receptor for AGE (sRAGE); AGE–RAGE stress; stressors; antistressors; glyoxalase 1; glyoxalase 2; AGER1; AGER2